Distraction osteogenesis as a treatment of obstructive sleep apnea syndrome: A systematic review. Issue 36 (September 2016) - Tsui, Wai Kin; Yang, Yanqi; Cheung, Lim Kwong; Leung, Yiu Yan
Abstract: Background: To conduct a systematic review to answer the clinical question "What are the effectiveness of mandibular distraction osteogenesis (MDO) and its complications to treat patients with obstructive sleep apnea syndrome (OSAS)?". Methods: A systematic search including a computer search with specific keywords, reference list search, and manual search were done. Relevant articles on MDO were assessed and selected in 3 rounds for final review based on 5 predefined inclusion criteria and followed by a round of critical appraisal. Different types of distraction and their treatment outcomes of OSAS were recorded with standardized form and analyzed. Results: Twelve articles were included in the final review. A total of 256 patients aged 7 days to 60 years were treated with either external or internal MDO, with a mean follow-up period of 6 to 37 months. The average distraction distance of 12 to 29 mm was achieved with various distraction protocols. The success rate for adult patients was 100%, and cure rates were ranged from 82% to 100%. The definition of success or cure for OSAS in children or infants was not defined. Therefore, there were no clearly reported success or cure rates for children/infants in the included studies. However, all studies reported that these patients showed significant improvement in OSAS, with many of them who avoided tracheostomy or had the tracheostomy decannulated. The complication rates were ranged from 0% to 21.4%, with most being from local wound infections or neurosensory disturbances. Conclusion: This systematic review showed that MDO was effective in resolving OSAS in adults with retrognathic mandible. MDO also showed promising results in infants or children with OSAS. From the results of this systematic review, we recommend to define the criteria of success or cure for OSAS surgery in children and infants. We also recommend setting up randomized controlled trials to compare MDO with traditional maxillomandibular advancement surgery for OSAS patients and to provide a better evidence on the success and complication rates of the techniques.